Continuous Flow Synthesis of High Valuable N-Heterocycles via Catalytic Conversion of Levulinic Acid - Rodríguez-Padrón, Daily; Puente-Santiago, Alain R.; Balu, Alina M.; Muñoz-Batista, Mario J.; Luque, Rafael (Frontiers in Chemistry, 2019)
Graphitic carbon nitride (g-C3N4) was successfully functionalized with a low platinum loading to give rise to an effective and stable catalytic material. The synthesized g-C3N4/Pt was fully characterized by XRD, N2 physisorption, XPS, SEM-Mapping and TEM techniques. Remarkably, XPS analysis revealed that Pt was in a dominant metallic state. In addition, XPS together with XRD and N2 physisorption measurements indicated that the g-C3N4 preserves its native structure after the platinum deposition process. g-C3N4/Pt was applied to the catalytic conversion of levulinic acid to N-heterocycles under continuous flow conditions. Reaction parameters (temperature, pressure and concentration of levulinic acid) were studied using 3 level for each parameter, and the best conditions were applied for the analysis of the catalyst stability. The catalytic system displayed high selectivity to 1‑ethyl-5-methylpyrrolidin-2-one and outstanding stability after 3 h of reaction.